Toward customer-centric power grid : Residential EV charging simulator for smart homes - Jäntti, Maarit; Jäntti, Anssi; Shafie-khah, Miadreza (Elsevier, Academic Press, 2022)
The role of the end users in the energy markets is changing from passive consumers to active prosumers, hence new solutions in the energy markets need to be designed in a user-centric way. This chapter focuses on the transition toward decentralized power grids where the role of consumers in making a decision is significant. In this context, a smart home demand response simulator is presented. The smart home includes an electric vehicle, and the EV charging simulator program is developed for the economics of charging an electric car under different conditions based on the habits of the user. The model contains several profiles related to power economics, and the implications of these can be evaluated under the specified conditions.
Keywords: Demand response; Smart home; Electric vehicle; Charging station; smart grid; fi=Sähkötekniikka|en=Electrical Engineering|